Determinants of Physical Activity Among Southeast Asian Adults: A Systematic Review - Abadini, D; Adriani, M; Endah Wuryaningsih, C (KnE Life Sciences, 2019)
Regular physical activity provides a lot of benefit to maintain good health and reduce the risk of non-communicable diseases. Recently Southeast Asia faces an epidemic of chronic non-communicable disease that responsible for 60% of deaths in the region. Physical inactivity has been reported as one of the causes related to non-communicable disease in adults. Research about determinants become as the first attempt to design intervention on physical activity. The attention to this topic has been widely spread in western countries, but not yet in Southeast Asia. This study aimed to gather knowledge about physical activity determinants and correlations from studies held among adults in Southeast Asia. Thus, it would provide an understanding about factors that related to Southeast Asian adult physical activity behavior and a guideline to extend study why were some people active but some other not. This study used a systematic review by using PRISMA 2009. Online database (Pubmed and Google Scholar) was used to find a relevant article contain determinant, correlate, or factors affecting physical activity among adults in Southeast Asia countries. The result from 8 studies in Southeast Asia countries showed some determinants of physical activity such as socio-demographic factors, psychological factors (perceived benefits, self-efficacy, self-regulation) and health status. It showed that physical activity was associated with age, education, marital status, income, job characteristic and living in urban or rural. The perceived benefit, greater self-efficacy, and self-regulation obtained participation in physical activity. Moreover, diagnosis with hypercholesterolemia was also associated with physical activity. Understanding determinants factors could be a contribution for public health to design programs and policy that increase physical activity participation among Southeast Asians adults. Keywords: physical activity, determinants, adults, Southeast Asia